Impaired Cerebrovascular Function in Coronary Artery Disease Patients and Recovery Following Cardiac Rehabilitation - Anazodo, Udunna C.; Shoemaker, J. K.; Suskin, Neville; Ssali, Tracy; Wang, Danny J. J.; St. Lawrence, Keith S. (Frontiers in Aging Neuroscience, 2016)
Coronary artery disease (CAD) poses a risk to the cerebrovascular function of older adults and has been linked to impaired cognitive abilities. Using magnetic resonance perfusion imaging, we investigated changes in resting cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) to hypercapnia in 34 coronary artery disease (CAD) patients and 21 age-matched controls. Gray matter volume images were acquired and used as a confounding variable to separate changes in structure from function. Compared to healthy controls, CAD patients demonstrated reduced CBF in the superior frontal, anterior cingulate, insular, pre- and post-central gyri, middle temporal and superior temporal regions. Subsequent analysis of these regions demonstrated decreased CVR in the anterior cingulate, insula, postcentral and superior frontal regions. Except in the superior frontal and precentral regions, regional reductions in CBF and CVR were identified in brain areas where no detectable reductions in gray matter volume were observed, demonstrating that these vascular changes were independent of brain atrophy. Because aerobic fitness training can improve brain function, potential changes in regional CBF were investigated in the CAD patients after completion of a 6-month exercise-based cardiac rehabilitation program. Increased CBF was observed in the bilateral anterior cingulate, as well as recovery of CBF in the dorsal aspect of the right anterior cingulate, where the magnitude of increased CBF was roughly equal to the reduction in CBF at baseline compared to controls. These exercise-related improvements in CBF in the anterior cingulate is intriguing given the role of this area in cognitive processing and regulation of cardiovascular autonomic control.